حضور المنهج السيميائي في مجلة السيميائيات العدد 19- - حواس، امنة; فار، ايمن; جابر، اية; بك، عبد العزيز; تواتي، يسمينة (University of Eloued جامعة الوادي, 2025)
تتناول هذه الدراسة حضور المنهج السيميائي في العدد 19 من مجلة "سيميائيات"، مركّزةً على مدى توظيف الباحثين العرب لهذا المنهج في مقارباتهم النقدية، وكيفية تأقلمهم مع أدواته ومفاهيمه في تحليل النصوص العربية. وقد استندت الدراسة إلى المنهج التحليلي الوصفي في تحليل مضمون مقالات المجلة. يتكون العمل من قسمين رئيسيين: 1. فصل نظري يعرض الأسس المعرفية للمنهج السيميائي، نشأته، تطوره، وأدواته مثل العلامة، الإشارة، التأويل، التمفصل المزدوج والتركيب الدلالي. 2. فصل تطبيقي يتضمن تحليل ثلاث مقالات منشورة في العدد الأول من مجلد 19 للمجلة: o دراسة حول المصطلح السيميائي وأبعاده المعرفية والثقافية. o دراسة سيميائية لصورة المجتمع الجزائري من خلال مسلسل "الدامة". o تحليل سيميائي للفضاء الروائي في رواية "براري الموت" لمرزاق بقطاش. أبرز النتائج: • المنهج السيميائي حاضر بقوة في دراسات العدد، وتم توظيفه لتحليل النصوص الأدبية والمرئية بعمق. • أظهر الباحثون العرب وعياً متزايداً بالمصطلحات السيميائية وأثر السياقات الثقافية على دلالاتها. • تم اعتماد أدوات سيميائية دقيقة مثل التأويل، العلامة، الصورة، الفضاء، والزمن السردي لفهم النصوص وتحليلها. • الدعوة إلى تطوير معاجم متخصصة بالمصطلحات السيميائية وتعريبها وفق معايير دقيقة. الكلمات المفتاحية باللغة العربية : ا Résumé This study explores the presence of the semiotic approach in Issue 19 of the journal Sémiotiqués, focusing on how Arab researchers have adopted and adapted semiotic tools and concepts to analyze Arabic texts. The research employs a descriptive-analytical method to examine the content of selected articles from the journal. The structure of the work includes two main sections: 1. Theoretical Chapter – It presents the epistemological foundations of semiotics, its origins, development, and analytical tools such as the sign, signal, interpretation, double articulation, and semantic structure. 2. Applied Chapter – This section analyzes three articles published in the first issue of Volume 19 of the journal: o A study on the semiotic term and its cognitive and cultural dimensions. o A semiotic analysis of Algerian society’s image in the TV series El Dama. o A semiotic reading of narrative space in the novel Wilderness of Death by Merzak Bagtache. Key Findings: • The semiotic method is prominently applied in the studies of this issue and is effectively used to analyze both literary and visual texts. • Arab researchers have demonstrated growing awareness of semiotic terminology and the impact of cultural context on meaning. • Analytical tools such as interpretation, signs, imagery, narrative space, and narrative time were used precisely to uncover textual meanings. • The study advocates for the development of specialized glossaries for semiotic terminology and the Arabization of terms following rigorous criteria.
مذكرة ليسانس.نقد ومناهج.2025
Keywords: Semiotics; semiotic method; Sémiotiqués journal; sign; interpretation; narrative space; TV drama; discourse analysis; narrative time; critical terminology; visual culture.; لسيميائية، المنهج السيميائي، مجلة سيميائيات، العلامة، التأويل، الفضاء الروائي، الدراما التلفزيونية، تحليل الخطاب، الزمن السردي، المصطلح النقدي، الثقافة البصرية.